2014
DOI: 10.1371/journal.ppat.1003845
|View full text |Cite|
|
Sign up to set email alerts
|

Suppression of Interferon Lambda Signaling by SOCS-1 Results in Their Excessive Production during Influenza Virus Infection

Abstract: Innate cytokine response provides the first line of defense against influenza virus infection. However, excessive production of cytokines appears to be critical in the pathogenesis of influenza virus. Interferon lambdas (IFN-λ) have been shown to be overproduced during influenza virus infection, but the precise pathogenic processes of IFN-λ production have yet to be characterized. In this report, we observed that influenza virus induced robust expression of IFN-λ in alveolar epithelial cells (A549) mainly thro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
89
0
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 104 publications
(97 citation statements)
references
References 59 publications
6
89
0
2
Order By: Relevance
“…However, in our case the immune stimulation by shM did not result in inhibition of IAV replication. Our results confirmed that IFN-λ could play a critical role in the pathogenesis of IAV and IFN-λ was induced through a RIG-1 -dependent pathway (Svetlikova et al, 2010;Okamoto et al, 2014;Wei et al, 2014). We conclude that shRNAs inhibited influenza virus infection in a gene-specific manner in cooperation with IFN-λ.…”
Section: Discussionsupporting
confidence: 80%
“…However, in our case the immune stimulation by shM did not result in inhibition of IAV replication. Our results confirmed that IFN-λ could play a critical role in the pathogenesis of IAV and IFN-λ was induced through a RIG-1 -dependent pathway (Svetlikova et al, 2010;Okamoto et al, 2014;Wei et al, 2014). We conclude that shRNAs inhibited influenza virus infection in a gene-specific manner in cooperation with IFN-λ.…”
Section: Discussionsupporting
confidence: 80%
“…In comparison with IFN-α, IFN-λ is predominantly induced by respiratory viruses (2831). Currently, IFN-λ is designated as a therapeutic candidate against the influenza A virus (IAV) infection (32, 33).…”
Section: Role Of Ifn-λ In the Control Of Viral Infections Of The Respmentioning
confidence: 99%
“…NS1 and NS2 proteins of the human RSV also inhibit IFN-λ production, occurring via IFN regulatory factor (IRF)-3, NF-κB, and proinflammatory cytokines suppression (36, 37). More recently, it has been reported that excessive expression of IFN-λ in the lung during IAV infection is associated with a suppression of IFN-λ signaling by SOCS-1 (31). The authors suggested that the suppression of cytokine signaling by virus-induced SOCS-1 leads to an adaptive increase in IFN-λ production by the host to protect cells against viral infection.…”
Section: Role Of Ifn-λ In the Control Of Viral Infections Of The Respmentioning
confidence: 99%
“…The interplay between influenza A virus and host innate immune signaling pathways has clearly been revealed to a great extent (16)(17)(18), but the regulatory mechanism of influenza B virus infection awaits further investigation. Currently, fundamental research has elucidated the interrelationship between influenza B virus and the host innate immune system.…”
mentioning
confidence: 99%